Democratic Citizenship of Teacher Movement in Indonesia Post-Soeharto: Between Democratic Citizenship and Civic Engagement - Hidayat, Rakhmat (Jurnal Ilmiah Peuradeun, 2018)
After May 1998, Indonesia began the transition from centralization to the era of autonomy. During 32 years, Soeharto’s New Order regime (1966-1998) demonstrated authoritarian regime in many sectors, like politics, economics, social, especially in education. The political freedom of the Reform era has opened up an opportunity for the revival of social movements in Indonesia. Reform has enabled more open political structure, including a friendlier political atmosphere for the teacher movement. The purpose of this research is to explain how teacher movement in Indonesia made transformation from authoritarian which close movement to liberal with open movement. In New Order regime with authoritarian performance, Persatuan Guru Republik Indonesia (Teacher Union in Indonesia) is as the single actor. The paper discussed three main aspects: (1) the explanation of the emerging of teacher movements in the process of democratic citizenship (2) the dynamics of teacher movement in developing teacher capacity in era of decentralization of Indonesia (3) the relations of teacher movement between the civil societies in era of decentralization. The teacher movement influences Indonesia’s democratization process. Teacher movement has contributed substantially in increasing participation and democracy in Indonesia, building the legal and institutional infrastructure for democracy, and providing voice and educational advocacy in supporting the reform.